Astrovirus in the Brazilian Amazon: First detection of non-classical astroviruses (MLB-3) in the Americas - Dan Santos Alves; Dielle Monteiro Teixeira; Edivaldo Costa Sousa Junior; Danielle Rodrigues de Deus; Patrícia dos Santos Lobo; Sylvia de Fátima dos Santos Guerra; Luciana Damascena da Silva; Hugo Reis Resque; Luana Silva Soares; Yvone Benchimol Gabbay; Jones Anderson Monteiro Siqueira (PLoS ONE, 2026)
Human astrovirus (HAstV) is a viral agent responsible for acute gastroenteritis (AGE), primarily affecting children and the elderly worldwide. Belonging to the Astroviridae family, HAstV is classified into eight classical serotypes (HAstV 1–8) and two other divergent non-classical clades: Melbourne (MLB 1–3) and Virginia (VA 1–6), which have been associated with gastroenteritis, central nervous system complications, and acute respiratory disease. This study aimed to investigate the frequency of classical and non-classical HAstV in fecal specimens collected from children up to 14 years of age in northern Brazil, within the Amazon region, between 2013 and 2022. A total of 560 samples, all previously tested negative for other gastroenteric viruses such as rotavirus and norovirus, were analyzed using reverse transcription followed by quantitative polymerase chain reaction (RT-qPCR) and conventional RT-PCR. For classical HAstV, 10.7% (60/560) of the samples were positive by RT-qPCR and 2.0% (11/560) to 3.0% (17/560) by conventional RT-PCR using different primers set. Non-classical HAstV was detected in 0.2% (1/560) of the samples. Diarrhea was present in 91.7% of positive cases, vomiting in 71.7%, and fever in 53.3%. The most affected age group was children aged >5–10 years (25.0%), with no significant association between infection rate and sex. A higher number of infections occurred during the Amazon winter (11.6%), with Roraima identified as the federative unit with the highest number of cases. Fifteen samples (88.2%, 15/17) were sequenced and identified as classical HAstV, with the following genotypes detected: HAstV-1 (60.0%, 9/15), HAstV-3 (20.0%, 3/15), and HAstV-4 (20.0%, 3/15). Non-classical HAstV sequencing was performed on 12 (93.2%, 12/13) positive specimens, characterized as HAstV-1 (50%, 6/12), HAstV-3 (25%, 3/12), HAstV-4 (16.7%, 2/12), and HAstV-MLB-3 (8.3%, 1/12). A probable recombinant strain was identified, classified as HAstV-4 based on the ORF2 region and HAstV-1 based on the ORF1b region. This study provides updated epidemiological data on HAstV in the Brazilian Amazon and highlights the genetic diversity of both classical and non-classical genotypes. Notably, it reports the first detection – and the second complete genome repository – of the rare MLB-3 genotype in the Americas.